A Supramolecular Palladium Catalyst Displaying Substrate Selectivity by Remote Control. Issue 2 (11th December 2018) - Zardi, Paolo; Roisnel, Thierry; Gramage‐Doria, Rafael
Abstract: Inspired by enzymes such as cytochrome P‐450, the study of the reactivity of metalloporphyrins continues to attract major interest in the field of homogeneous catalysis. However, little is known about benefitting from the substrate‐recognition properties of porphyrins containing additional, catalytically relevant active sites. Herein, such an approach is introduced by using supramolecular ligands derived from metalloporphyrins customized with rigid, palladium‐coordinating nitrile groups. According to different studies (NMR and UV/Vis spectroscopy, XRD, control experiments), the supramolecular ligands are able to accommodate pyridine derivatives as substrates inside the porphyrin pocket while the reactivity occurs at the peripheral side. By simply tuning a remote metal center, different binding events result in different catalyst reactivity, and this enzyme‐like feature leads to high degrees of substrate selectivity in representative palladium‐catalyzed Suzuki–Miyaura reactions. Abstract : Ground control : Supramolecular catalysts based on porphyrin scaffolds with peripheral palladium ions (see figure) modulate the reactivity of structurally similar substrates by tuning the properties of the binding site (A ), which is eight chemical bonds apart from the active site (Pd ).